Missionary lingustics II = Lingüí́stica misionera II : orthography and phonology : selected papers from the Second International Conference on Missionary Linguistics, São Paulo, 10-13 March 2004. - Zwartjes, Otto; Altman, Maria Cristina Salles (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences,, 2005)
This is the second volume to be dedicated to the pioneering linguistic work produced by the religious missionaries who, within the scope of the European colonial enterprises along the period 1550–1850, described dozens of autochthonous languages, many of which are only known today thanks to their endeavours. The twelve papers joint in the present volume — which dedicated special attention to the orthographical and phonological dimension of their work — provide a comprehensive picture of the descriptive problems faced by these linguists avant la lettre, notably: the difficulties faced before the less familiar features of these languages, such as vowel quantity, accentuation, tonality, nasalization, glottalization, ‘gutturalization’; the building of (re)definitions and the creation of a new metalanguage, like ‘saltillo’, ‘guturaciones’, etc.; The book elucidates the creativity and innovations proposed by individual missionaries and the instructive and pedagogical dimension of their work.